ПСОРИАЗ КОРРЕКЦИЯ МЕТОДОВ ЛЕЧЕНИЯ - Дилмурадова К.Р , (TADQIQOTLAR.UZ, 2024)
Abstract: This review article is devoted to the role of glycosaminoglycans (GAGs) in the treatment of psoriasis. Psoriasis is a chronic inflammatory skin disease characterized by hyperproliferation of keratinocytes and inflammation. In recent years, considerable attention has been paid to research into the use of GAGs, such as chondroitin sulfate, hyaluronic acid, etc., as potential therapeutic agents for improving the symptoms of psoriasis. Analysis of literature data allows us to evaluate the effectiveness and mechanisms of action of these compounds in the context of psoriatic pathogenesis.